Quantitative contributions of TNF receptor superfamily members to CD8+ T‐cell responses. Issue 11 (22nd November 2021) - Nguyen, John; Pettmann, Johannes; Kruger, Philipp; Dushek, Omer
Abstract: T‐cell responses to infections and cancers are regulated by co‐signalling receptors grouped into the binary categories of co‐stimulation or co‐inhibition. The co‐stimulation TNF receptor superfamily (TNFRSF) members 4‐1BB, CD27, GITR and OX40 have similar signalling mechanisms raising the question of whether they have similar impacts on T‐cell responses. Here, we screened for the quantitative impact of these TNFRSFs on primary human CD8 + T‐cell cytokine production. Although both 4‐1BB and CD27 increased production, only 4‐1BB was able to prolong the duration over which cytokine was produced, and both had only modest effects on antigen sensitivity. An operational model explained these different phenotypes using shared signalling based on the surface expression of 4‐1BB being regulated through signalling feedback. The model predicted and experiments confirmed that CD27 co‐stimulation increases 4‐1BB expression and subsequent 4‐1BB co‐stimulation. GITR and OX40 displayed only minor effects on their own but, like 4‐1BB, CD27 could enhance GITR expression and subsequent GITR co‐stimulation. Thus, different co‐stimulation receptors can have different quantitative effects allowing for synergy and fine‐tuning of T‐cell responses. SYNOPSIS: Experimental measurements of T‐cell responses and mathematical modellings are used to quantitatively investigate the impact of 4‐1BB, CD27, GITR and OX40 co‐stimulation on primary human CD8 + T‐cell cytokine production. While both 4‐1BB and CD27 increased cytokine production, only 4‐1BB increased the duration over which cytokine is produced. A mathematical model reproduces these differences based on shared signalling but different surface receptor regulations. The model predicted a synergy between CD27 and 4‐1BB/GITR due to CD27‐induced increase in 4‐1BB/GITR surface expression, which was validated experimentally. Abstract : Experimental measurements of T‐cell responses and mathematical modellings are used to quantitatively investigate the impact of 4‐1BB, CD27, GITR and OX40 co‐stimulation on primary human CD8 + T‐cell cytokine production.